The Arrest and Sentencing of Jesus: A Historical Reconstruction - Cunningham, Philip A. (The journal of religion and film, 2004)
I will approach the subject using official Catholic teaching as the starting point for a consideration of our primary sources of information, the four Gospel passion narratives. By examining three scenes in the passion story and comparing what the different Gospel accounts describe, I will offer some conclusions about the historical events that lie behind them. These conclusions are fairly widely agreed upon in contemporary scripture scholarship. As one of the professors invited by the Secretariat of Ecumenical and Interreligious Affairs of the U.S. Conference of Catholic Bishops to read a shooting script of Mel Gibson's The Passion of the Christ, it is appropriate for me to proceed in this way. At that time, I was primarily concerned to see if the shooting script conformed to Catholic teaching on the nature of the Gospels and in particular on the proper interpretation of the passion narratives.